ROLE OF CONTRAST-ENHANCED CT PARANASAL SINUSES IN DIAGNOSING RHINOSINOMUCORMYCOSIS IN POST COVID PATIENTS - MAQSOOD , S; MUGHAL , HH (Biological and Clinical Sciences Research Journal, 2024)
Rhinosinomucormycosis is a life-threatening fungal infection that has emerged as a significant complication in post-COVID-19 patients, particularly in those with diabetes or corticosteroid use. Early diagnosis is critical, and contrast-enhanced CT (CECT) has proven valuable in detecting characteristic features of the disease. Objective: This study evaluates the role of CECT in diagnosing rhinosinomucormycosis in post-COVID patients in Pakistan. Methods: A retrospective observational study was conducted at a tertiary care hospital in Rawalpindi from March 2021 to September 2021. Ninety patients with clinical suspicion of rhinosinomucormycosis following COVID-19 were included. All patients underwent CECT of the paranasal sinuses, and imaging findings were correlated with histopathological results. Demographic data, risk factors, and clinical outcomes were also analyzed. Results: The sensitivity of CECT in diagnosing rhinosinomucormycosis was 95%. Common imaging findings included sinonasal mucosal thickening (86.7%), bone erosion (72.2%), intraorbital extension (53.3%), and intracranial extension (23.3%). Diabetes mellitus (71.1%) and corticosteroid use (70%) were the most prevalent risk factors. Patients with intraorbital or intracranial involvement had higher rates of complications, including surgical intervention (63.3%) and mortality (6.7%).Conclusion: Contrast-enhanced CT is a reliable diagnostic tool for rhinosinomucormycosis in post-COVID-19 patients, enabling early detection and management of the disease. Incorporating CECT into routine diagnostic protocols can significantly improve outcomes, particularly in high-risk populations in resource-constrained settings.